Comparison of the Computational Efficiency of Gradient-Type Methods in Optimal Control Problems - Antonik, V. G. (Journal of mathematical sciences (New York, N.Y.), 2024)
Estimating of the efficiency of iterative methods is determined by results of computational experiments on solving typical test and applied problems. In this paper, we present information on the numerical implementation of typical gradient methods in comparison with modifications proposed by the authors for the approximate solution of certain applied problems from chemical technology and electrical engineering.